Prevalence of cardiovascular events among patients with type 2 diabetes in the west region of Saudi Arabia - Abdullah A. Assiri; Khalid A. Alahmari; Nawaf S. Alqhtani; Nourah A. AlShamrani; Ali S. Mubarak; Khalid M. Alshehri; Adhari A. Alselmi, MD (Elsevier, 2022)
Background: Diabetes mellitus (DM) remains a concern globally and particularly in Saudi Arabia, where its prevalence is continuously increasing among the Saudi population. DM is known to increase the risk of cardiovascular disease (CVD), which can progress significantly if DM is poorly controlled. Aim: Determine the prevalence of cardiovascular events among patients with type 2 diabetes (T2DM) in the west region of Saudi Arabia, and additionally the use of antidiabetic agents with cardiovascular benefits (ADc) in T2DM patients with cardiovascular events (CVEs). Method: A retrospective cohort study was conducted among all patients with T2DM who presented to the diabetic center of Prince Mansour Military Hospital (PMMH), Taif city, between the 1st of January and 30th of June 2021. Data extracted from patient medical records included demographics, home medications, medications used to treat T2DM, lab results, and ECG data. Descriptive statistics were used to analyze and compare the results. The study was approved by the Research and Ethics Committee of Medical Services General Directorate, Armed Forces Hospitals, Taif region. Result: A total of 349 patients with T2DM were recruited and included in the final analysis. Of this study population, 132 patients had experienced at least one cardiovascular event while 54 were considered to be at risk of future cardiovascular events due to having risk factors for cardiovascular diseases above and beyond the presence of diabetes. A subgroup analysis was conducted to examine HbA1c% among all groups; interestingly, all were similar, with p > 0.05. Of all diabetic patients with CVEs, only 34.8 % were on at least one anti-diabetic agent known to have cardiovascular benefits; the remainder were on other anti-diabetic agents. A similar analysis was conducted on diabetic patients with risk of CVEs, of which only 13 % were on at least one anti-diabetic agent having known cardiovascular benefits; the remainder were on other anti-diabetic agents. Conclusion: The prevalence of CVEs among T2DM patients in Saudi Arabia is very close to the global prevalence, but ADcs are underutilized in this population. Tighter glycemic control is warranted to help rein in and reduce the CVE incidence among patients with T2DM.